2012
DOI: 10.1097/mpa.0b013e31823b66d3
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor β and Ras/MEK/ERK Signaling Regulate the Expression Level of a Novel Tumor Suppressor Lefty

Abstract: Our data suggest that Lefty is a novel TGF-β target molecule that mediates growth inhibition of pancreatic cancer cells. In addition, activation of the Ras/MEK/ERK pathway serves as a mechanism by which pancreatic cancer escapes from growth inhibition by the TGF-β-Lefty axis. The results imply a novel therapeutic strategy for pancreatic cancer, that is, combination treatment with Ras/MEK/ERK inhibitors and TGF-β.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 54 publications
5
19
0
Order By: Relevance
“…Given prior evidence of SMAD-independent MAPK activation downstream of TGF-␤ signaling (45,46), we hypothesize that the observed activation of TGF-␤ signaling might be a compensatory mechanism either partially or primarily aimed at SMAD-independent MAPK signaling activation upstream of RAS to counteract MAPK blockade produced by the inhibitors. These results provide further support for the argument that combination therapy with MAPK and TGF-␤ inhibitors may have potential benefits in the treatment of KRAS-driven cancers (50,51).…”
Section: Mib-prm Identifies Activation Of Tgf-␤ Signaling As a Compensupporting
confidence: 70%
“…Given prior evidence of SMAD-independent MAPK activation downstream of TGF-␤ signaling (45,46), we hypothesize that the observed activation of TGF-␤ signaling might be a compensatory mechanism either partially or primarily aimed at SMAD-independent MAPK signaling activation upstream of RAS to counteract MAPK blockade produced by the inhibitors. These results provide further support for the argument that combination therapy with MAPK and TGF-␤ inhibitors may have potential benefits in the treatment of KRAS-driven cancers (50,51).…”
Section: Mib-prm Identifies Activation Of Tgf-␤ Signaling As a Compensupporting
confidence: 70%
“…Lefty exerted an inhibitory effect on the tumor-promoting function of Nodal, as recombinant Lefty suppressed Nodal-mediated proliferation [17]. Western blot analysis also revealed that hESC-derived Lefty significantly diminished Nodal protein expression in C8161 and MDA-MB-231 cells [6].…”
Section: Introductionmentioning
confidence: 93%
“…We therefore investigated the effects of TGF‐β on Lefty expression in somatic cells. We recently reported that Lefty expression is induced by TGF‐β in several pancreatic cancer cell lines, all of which contained a ras mutation (12). We found that the canonical TGF‐β pathway is important for Lefty expression and that inhibition of ras‐MAPK signaling potentiates Lefty expression more than 10‐fold.…”
mentioning
confidence: 99%